2016
DOI: 10.5194/acp-16-6319-2016
|View full text |Cite
|
Sign up to set email alerts
|

Emission factors for gaseous and particulate pollutants from offshore diesel engine vessels in China

Abstract: Abstract. Shipping emissions have significant influence on atmospheric environment as well as human health, especially in coastal areas and the harbour districts. However, the contribution of shipping emissions on the environment in China still need to be clarified especially based on measurement data, with the large number ownership of vessels and the rapid developments of ports, international trade and shipbuilding industry. Pollutants in the gaseous phase (carbon monoxide, sulfur dioxide, nitrogen oxides, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
58
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 59 publications
12
58
1
Order By: Relevance
“…It was estimated that 8.4% of SO 2 and 11.3% of the total NO x emissions in China originated from ships in 2013. 52 It has been reported that 0.18 million water transport vessels and 1.07 million fishing boats were active in Chinese waters in 2013, of which one-third were in the Bohai Sea. 44 Thus, the increasing number of mobile sources observed on BH Island can also be attributed to ship emissions.…”
mentioning
confidence: 99%
“…It was estimated that 8.4% of SO 2 and 11.3% of the total NO x emissions in China originated from ships in 2013. 52 It has been reported that 0.18 million water transport vessels and 1.07 million fishing boats were active in Chinese waters in 2013, of which one-third were in the Bohai Sea. 44 Thus, the increasing number of mobile sources observed on BH Island can also be attributed to ship emissions.…”
mentioning
confidence: 99%
“…Actually, emission factors and the ratios of OC and EC at different engine loads have been discussed in our previous studies (Zhang et al, 2016;2018). In this study, we focused on the size-segregated OC and EC distributions.…”
Section: C3mentioning
confidence: 98%
“…All the abbreviations have been changed in the revised manuscript. Finally, due to the fact that our research on shipping emissions was a complete series, including the emission factors and characteristics of gaseous pollutants, PM and its chemical composition, the influence factor, the organic matters, and the total emissions in our previously published papers (Zhang et al, 2016(Zhang et al, , 2018(Zhang et al, , 2019, we would like to retain the specific ship…”
Section: Responsementioning
confidence: 99%
See 1 more Smart Citation
“…The time span between plume emission and measurement is also important for the measured NO 2 values because of NO to NO 2 titration, as a large fraction of nitrogen oxides (NO x ) is emitted as NO (Alföldy et al, 2013;Zhang et al, 2016), which does not absorb in the spectral range covered and cannot be measured with MAX-DOAS. Therefore, the NO 2 signal increases with distance from the ship and, depending on the wind direction, with distance from the ship track.…”
Section: "Onion Peeling" Max-doas Approachmentioning
confidence: 99%